2010
DOI: 10.1093/nar/gkq555
|View full text |Cite
|
Sign up to set email alerts
|

Vgl1, a multi-KH domain protein, is a novel component of the fission yeast stress granules required for cell survival under thermal stress

Abstract: Multiple KH-domain proteins, collectively known as vigilins, are evolutionarily highly conserved proteins that are present in eukaryotic organisms from yeast to metazoa. Proposed roles for vigilins include chromosome segregation, messenger RNA (mRNA) metabolism, translation and tRNA transport. As a step toward understanding its biological function, we have identified the fission yeast vigilin, designated Vgl1, and have investigated its role in cellular response to environmental stress. Unlike its counterpart i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 36 publications
5
53
0
Order By: Relevance
“…Cytoplasmic vigilin plays a key role in mRNA stabilization and positively regulates translation, notably in response to stress (17)(18)(19)46). Interestingly, we observed that CF airway neutrophils undergo marked changes in their transcriptional profile compared with CF blood neutrophils (Laval et al, manuscript in preparation), consistent with reprogramming (3,39).…”
Section: Discussionsupporting
confidence: 52%
“…Cytoplasmic vigilin plays a key role in mRNA stabilization and positively regulates translation, notably in response to stress (17)(18)(19)46). Interestingly, we observed that CF airway neutrophils undergo marked changes in their transcriptional profile compared with CF blood neutrophils (Laval et al, manuscript in preparation), consistent with reprogramming (3,39).…”
Section: Discussionsupporting
confidence: 52%
“…Despite the fact that yeast SGs seem to contain most if not all components of mammalian SGs, unlike the situation in mammals, their formation is independent of eIF2a phosphorylation in the budding yeast (Grousl et al 2009). Similarly, observations from fission yeast (Wen et al 2010;Nilsson and Sunnerhagen 2011) and trypanosomes (Kramer et al 2008) show that assemblies of SGs in response to heat shock are also independent of phosphorylation of eIF2a. It appears that other pathways contribute to formation of SGs in several organisms.…”
Section: Introductionmentioning
confidence: 79%
“…Polyribosomes were obtained as previously described (Wen et al 2010). CHX (100 mg/mL) was added to 50 mL of cultures at an OD 600 of 0.5 grown at 30°C.…”
Section: Polyribosome Profile Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Conditions for growth, maintenance, and genetic manipulation of fission yeast were as described previously (10). A complete list of the strains used in this study is given in Table S1 in the supplemental material.…”
Section: Methodsmentioning
confidence: 99%